Analysis of Customer Engagement towards Customer Loyalty through Customer Trust in Traditional Life Insurance Products in South Tangerang City - Kurniawaty, Erlita; Limakrisna, Nandan; Purba, Jan Horas V (Formosa Journal of Multidisciplinary Research, 2024)
The insurance services industry as a business of trust is still considered to have not fully gained the trust of its customers and the minimal involvement of its customers means that the reality is that customer loyalty is decreasing in terms of purchasing insurance products, especially traditional life insurance. Especially in the private sector as a guarantor institution that can provide protection for life. This study aims to test the effect of customer involvement on customer loyalty through customer trust. The approach used in this study is a quantitative approach. The population and sample used in this study were all customers who have traditional life insurance products in South Tangerang City, totaling 120 respondents with a sampling technique using the saturated sample method. The research data were obtained from the results of filling out the questionnaire and analyzed using the SEM analysis method technique with the help of the Lisrel program. The results of the study indicate that (1) Customer involvement has no effect on Customer Trust (2) Customer involvement has an effect on customer loyalty (3) Customer involvement has an effect on customer loyalty through customer trust.